Essential guide to cake decorating - Barker, Alex; Pressley, Sue; Steve, Moss; Turner, Paul (New york Parragon, 2009)
Essential guide to cake decorating explains and illustrates the equipment and required for making and decorating a variety of beautiful cakes
12
Keywords: Baking; Cake decorating; Desserts